Effect of Social Factors on Tuberculosis Patients: A Comprehensive Illness Behaviour Study - M, Ali; F, Imam; S, Mallik; RK, Mehra; P, Kumar; A, Garg (Indian Journal of Pharmacy Practice)
Aim: The aim of present study was to examine whether social factors can influence the illness behaviour of Tuberculosis patient. Comparison was done between tuberculosis patient (Case, Group I) with other Respiratory disease patient (Control, Group II) on the basis of illness behaviour questionnaire (IBQ) and search for possible differences between the two patient subgroups. Results: Number of patients enrolled for the study were 164. Out of which, 82 patients served as case (i.e. Group I) and 82 patients as control (i.e. Group II). The illness behaviour of tuberculosis patients was more in Joint family (57.32%) as compared to nuclear family (42.68 %). The illness behaviour was found to be highest where more than 3 people lived in a single room (34.15%). As TB is mostly prevalent in rural area, similarly illness behaviour was also observed highest in rural area (31.71%). The illness behaviour was more in married patients (64.63 %) in comparison with unmarried patients (35.37 %). Conclusion: The outcome of the present study indicates that low socio-economic status has great influence to invite illness behaviour in TB. Therefore, illness behaviour must be considered during the treatment of tuberculosis patients.
Keywords: Tuberculosis; Illness behaviour; Socio-economic; DOTS